A test for determining endurance capacity in fencers - Weichenberger, M.; Liu, Y.; Steinacker, J. M. (International Journal of Sports Medicine, 2012)
Until now endurance in fencers has been tested by non-specific ergometer tests even though the movement patterns during fencing are considerably different. The aim of the study was to evaluate a newly developed fencing-specific endurance test (FET). 2 studies were carried out: 28 fencers were tested by FET with fencing-specific footwork and incremental tests on cycle (CE) and treadmill ergometer (TM) in a random order. Afterwards fencing bouts (BOU) were conducted to determine specific physical load. Blood lactate and heart rates were measured. In a second study another group of 18 international and 20 national level fencers conducted FET to explore differences between groups. Comparison of CE, TM, FET and BOU revealed a significant correlation between FET and BOU (r=0.80, p<0.01), heart rates during CE and TM were significantly lower than in bouts (p<0.01). Performance at CE and TM hardly correlated with FET (r=0.30, p<0.05; r=0.31, p<0.05). Elite-fencers showed significantly better performance than non-elite fencers in FET (p<0.01). FET was suitable for determining specific endurance in fencers, allows a better assessment of physical demands during bouts than conventional ergometry and can be used to distinguish between fencers of different levels.